Reactive Species in Huntington Disease: Are They Really the Radicals You Want to Catch? - José Bono-Yagüe; Ana Pilar Gómez-Escribano; José María Millán; Rafael Pascual Vázquez-Manrique (MDPI AG, 2020)
Huntington disease (HD) is a neurodegenerative condition and one of the so-called rare or minority diseases, due to its low prevalence (affecting 1-10 of every 100,000 people in western countries). The causative gene, HTT, encodes huntingtin, a protein with a yet unknown function. Mutant huntingtin causes a range of phenotypes, including oxidative stress and the activation of microglia and astrocytes, which leads to chronic inflammation of the brain. Although substantial efforts have been made to find a cure for HD, there is currently no medical intervention able to stop or even delay progression of the disease. Among the many targets of therapeutic intervention, oxidative stress and inflammation have been extensively studied and some clinical trials have been promoted to target them. In the present work, we review the basic research on oxidative stress in HD and the strategies used to fight it. Many of the strategies to reduce the phenotypes associated with oxidative stress have produced positive results, yet no substantial functional recovery has been observed in animal models or patients with the disease. We discuss possible explanations for this and suggest potential ways to overcome it.